PANASONIC ELECTRONIC PRODUCT DESIGN WEBSITE Using Macro media Dreamweaver MX - Nurdiansyah Nurdiansyah; Melani Dewi Lusita, SKom.,MMSI (Jurnal Sistem Informasi, 2007)
Website designing electronic products are made by Panasonic using MacromediaDreamweaver MX application program whose goal is to create a website that displaysvarious information about products which can be accessed electronically crowd, and thatconsumers who want buy electronics goods get references before buying electronic goods.Use Table, Link and others in making this program a facility has been provided byMacromedia Dreamweaver MX for in making it easy to create a web page.Bibliography : (Vii + 37 + Appendix) (1996 - 2006)Keywords: Website, Electronic, Products, Panasonic, Dreamweaver MX.